Analysis of meteorological and terrain features leading to the Izmir flash flood, 3-4 November 1995 - Komuscu, Ali Umran; Celik, Seyfullah; Erkan, Ayhan (1998)
Flash floods associated with heavy precipitation has become a hazardous phenomenon along the Mediterranean coasts of Turkey in recent years. During 3 and 4 November 1995 heavy and intense rainstorm activity over the Aegean coast led to flash flooding in the city of Izmir. Damage exceeded $50 million and 61 people died as a result of the flood. The Karsiyaka district suffered the most severe damage. This study presents an analysis of the meteorological settings that led to the development of these intense storms and describes the role of the terrain features involved in the Izmir flood. The important mesoscale features which initiated the severe weather outbreak included pronounced low-level advection, positive vorticity and strong upper level divergence. A surface low centered over the Aegean Sea enhanced the advection of warm and moist unstable air masses coming from the southwest over the Mediterranean Sea along a southwesterly low level jet (LLJ). A squall line oriented NE-SW over the Aegean Sea also contributed to the storm development, and intensity of the storms was further enhanced by the orographic effect. The presence of a frontal system, the stabaility indices associated with the event, and other meteorological features are all reminiscent of the synoptic type flash floods identified by Maddox. While the pressure and moisture patterns were favourable for severe storm activity, nonmeteorological factors including the topography, geomporphology, and land-use contributed to the flooding to a great extent. Settling in the flood-prone zone, insufficient floodwater structures, and the lack of channel improvements in the creeks enhanced flood damage to the city. Many of the deaths occurred in the settlements located in the flood-prone zone of the Ilica and Dallik creeks. - Reproduced
Keywords: Aegean coast; Izmir; Flood prone zone; Convective rainfall; Orographic lifting; Low level advection; Flash flooding